ANALISIS KONSEP PENGEMBALIAN PERSEPULUHAN OLEH KARYAWAN RUMAH SAKIT ADVENT BANDUNG YANG BERGEREJA DI JEMAAT CIHAMPELAS BANDUNG BERDASARKAN MALEAKHI 3:10 - Yultrismen Simanungkalit; Milton T. Pardosi (Jurnal Koinonia, 2016)
In this survey, the author examined the understanding of the concept of returning based on Malachi 3:10. The author focuses the research on employees of Adventist Bandung Hospital who are members of Jemaat Cihampelas Bandung. The survey is based on four main indicators, namely; theology of tithing, the purpose of returning tithe; how to calculate the tithe, and the meaning of “storehouse.”Frequently there are still some people who do not understand these issues, as the consequences, the concept of returning tithe is not practiced well. This study is divided into two parts, namely the study of the theory and field research. The results of theoretical research on the concept of returning tithe based on Malachi 3:10 is divided into three parts: First, the theology of tithe, tithe God's possession and must be returned to Him for it belongs to Him. The purpose is to be used for God’s work. The second, the purpose of this a statement of appreciation for the unselfish and help the servants of God to preach the gospel to the whole world. The third is how to calculate tithe? This calculated from the gross income figure, for example, shops, shoe companies, store pharmacies. And net income, for example, is pastors, mission employees, and government officials(permanent workers or employees). The fourth “storehouse” namely, the tithe is given where a member is served by ministers or pastors a church where a member regularly attends its worship. The results of field research conducted through a questionnaire distributed to employees of Bandung Adventist Hospital church that are members of Jemaat Cihampelas Bandungwhich produces an average of data that respondents understand well the theology of tithe. Results of research on the purpose of tithe to the average price of respondents understand well but, in P5 with the statement that the tithe is given to others in responding to ministry hesitation. Third, regarding the storehouse that is the tithe is given where members are served by servants of God with the tithe P8 that we should give to the church in our homeland, the results of this research they replied with hesitation. Results of research on how to calculate the tithe to the average of respondents are still undecided understand this with P6 statement that tithing should we give to a church in our homeland